Surgical Alternatives in the Treatment of Intestinal Intussusceptions Resulting from Polyps in Adults. Issue 9 (September 2013) - Arikanoglu, Zulfu; Onder, Akin; Taskesen, Fatih; Aliosmanoglu, Ibrahim; Gul, Mesut; Gumus, Hatice; Tas, Ilhan; Girgin, Sadullah
Adult intussusception is an uncommon disease requiring surgical intervention. The aim of this study is to discuss the surgical alternatives and share our experience in the treatment of adult patients with intussusceptions formed as a result of polyps. The retrospective study included 16 adult patients who underwent surgery after the diagnosis of intestinal invaginations resulting from polyps between the years 2000 and 2011. Sixteen patients (seven males and nine females; mean age, 48.18 years; range, 18 to 76 years) presented with intestinal intussusceptions. Although a preoperative diagnosis was carried out in 11 (68.75%) patients, the diagnosis was made intra-operatively in five patients (31.25%). Among the patients, seven (43.8%) had undergone emergency surgeries and nine (52.8) had elective surgery. The invagination in 12 patients (75%) was located in the small intestine, in two patients (12.5%) in the colon, and in a further two patients (12.5%), it was ileocecally located. Ten patients (62.5%) had segmental resection 1 anastomosis; three patients underwent (18.8%) segmental resection 1 enterostomy, and three (18.8%) received hemicolectomies. In adults, surgical treatment is always the primary option in intussusceptions resulting from polyps. Although the surgical method of choice in colonically located ones is en bloc resection without reduction, because the polyps located in the small intestine are usually of a benign nature, segmental resection with reduction should be performed in elective surgery and segmental resection without reduction should be performed in emergency cases.